The Efficacy and Safety of Cilostazol vs. Aspirin for Secondary Stroke Prevention: A Systematic Review and Meta-Analysis - Chai, Erqing; Chen, Jinhua; Li, Changqing; Zhang, Xue; Fan, Zhiqiang; Yang, Shijie; Zhao, Kaixuan; Li, Wei; Xiao, Zaixing; Zhang, Yichuan; Tang, Futian (Frontiers in Neurology, 2022)
Background Cilostazol is often used in Asia-Pacific countries for stroke prevention. The current systematic review and meta-analysis aimed to evaluate the effectiveness, safety, and adverse outcomes of cilostazol monotherapy compared to aspirin monotherapy for secondary stroke prevention. Methods The researchers conducted a comprehensive research in multiple databases (PubMed, Embase, and Cochrane library) of randomized controlled trials from conception to December 2020. The primary efficacy outcome was the occurrence of any stroke, the primary safety outcome was the bleeding risk, and the primary adverse outcome was the rate of headache and dizziness. The Mantel-Haenszel method was used to calculate a random-effects prediction. Cilostazol and aspirin were compared using a pooled risk assessment with 95% CIs. Results Six studies involving 5,617 patients were included in this review. Compared with aspirin monotherapy, cilostazol was associated with significantly lower rates of any strokes (RR: 0.67; 95% CI: 0.55–0.82) and significantly lower bleeding rates [risk ratio (RR): 0.53; 95% CI: 0.37–0.74]. However, compared with aspirin monotherapy, cilostazol was associated with significantly higher rates of headache (RR: 1.77; 95% CI: 1.41–2.20) and dizziness (RR: 1.28; 95% CI: 1.08–1.52). Conclusions Consistent with previous studies, cilostazol monotherapy is superior to aspirin monotherapy in reducing the rate of any strokes and the bleeding risk after having a stroke. However, the use of cilostazol monotherapy is associated with several adverse life outcomes such as headaches and dizziness.